Pawnbroking as instrument of partisan politics: The Municipal Bank of the City of Buenos Aires during the Radical Administration (1916-1930) (Quinto Sol, 2021)
The Banco Municipal de Préstamos y Cajas de Ahorro of the city of Buenos Aires, which was born in 1878 as Monte de Piedad as an institution to help the poorest with pawnbroking loans, underwent significant transformations in its functioning during the period of radicalism from 1916 to 1930. Originally, its almost exclusive function was that of the pledge of goods. From 1904 onwards, the opening of savings banks began and allowed the creation of a key source of financing. The radical administrations, which began with Hipólito Yrigoyen's triumph in 1916, continued and deepened the Bank's traditional social action role, although they linked it to the party's activity. This led to a political conflict between the Intendancy and the Deliberative Council, especially on the part of the socialist representatives. In parallel, the Bank experienced a strong expansion in its profits and capital in the 1920s. As a result of this growth, the government attempted to turn it into its lender and financial agent, a project that was completed in the early 1930, to transform it not only into the city's financial agent but also into a commercial entity.
Keywords: economic history; political history; pawnbroking loan; radicalism